Nature-based solutions using Leca® as a way to increase urban sustainable development and contribute to stormwater management - Monteiro, Cristina M. (2022)
In recent decades, the increase of building systems and the consequent impermeabilization of the inner-city environment, poses several negative environmental risks, especially those regarding global warming and water management. The long-term sustainability of urban development requires the adequate planning, inclusion and management of green spaces within urban areas. Urban green infrastructure provides benefits to urban inhabitants and the ecosystem, but their potential depends on their suitable implementation, integration and management as a comprehensive part of the urban environment, under the responsibility of different stakeholders. Nature-based solutions (NbS) are defined as systems inspired and supported by Nature and appears as an effective means to restore vegetation in densely populated areas contributing to its resilience. The use of NbS infrastructure within an urban environment helps to manage stormwater in reducing flood incidences when extreme precipitation events occur, furthermore contributing to the mitigation of the urban heat island effect and air pollution reduction. Several NbS such as green roofs and green walls, rain gardens, infiltration trenches and permeable pavements, are being implemented worldwide as an effective strategy to improve the environmental performance of densely populated urban cities. Lightweight Expanded Clay Aggregate (LECA®) has been widely incorporated in several innovative urban green infrastructure solutions due to their key characteristics (e.g. lightweight, porosity and good drainage), providing key components in stormwater management and water quality. This chapter aims to report and describe the potential influence that several NbS such as infiltration trenches, rain gardens and permeable pavements have on urban stormwater management (namely quantity and quality), considering several case studies using Leca® LWA - demonstrating their engineering benefits, innovative properties and overall contribution to the resilience and sustainability of urban areas.